Effects of Antenatal Magnesium Sulfate on the Gut Function of Preterm (<32 weeks) Very Low Birth Weight Neonates: Experience from a Tertiary Institute in South India. (7th June 2021) - Chandran, Shanu; Tergestina, Mintoo; Ross, Benjamin; Joshi, Avadhesh; Rebekah, Grace; Kumar, Manish
Abstract: Objective: Antenatal magnesium sulfate (MgSO4 ) is found to have various adverse effects in newborn, but the effect on preterm gut is still unclear. This study aimed to evaluate the effects of antenatal MgSO4 on preterm gut function by assessing the clinical outcomes and mesenteric blood flow. Methods: This was a prospective cohort study on all preterm very low birth weight (VLBW) neonates born at a tertiary care center in South India from November 2016 to August 2017. Neonates with antenatal magnesium (Mg) exposure were compared with those with no exposure for various neonatal outcome variables like time to reach full feeds, feed intolerance, necrotizing enterocolitis (NEC) and other preterm complications, serial serum Mg levels and superior mesenteric artery (SMA) Doppler velocity measurements at two time points (24–48 h and 4–5 days after birth). Results: Out of 84 neonates, 56 neonates were exposed to antenatal Mg with a median cumulative maternal dose of 28 g and the rest 28 neonates had no exposure. The mean time to reach full feeds was the same in both groups (10.5 days). Feed intolerance episodes were similar in the first week of life between the exposed and unexposed groups (48.2% vs. 46.4%; p  = 0.88). Univariate analysis revealed no difference between groups concerning rates of NEC ( p  = 0.17) or mortality ( p  = 0.39). There was no significant difference in SMA Doppler parameters and hypermagnesemia between the two groups. Conclusion: Our study found no significant impact on postnatal feed tolerance and mesenteric blood flow among preterm VLBW neonates with antenatal MgSO4 exposure.